Political Perspective on Technology Alliances – the Case of Microsoft and Google - Krzysztof Klincewicz (Journal of Entrepreneurship, Management and Innovation)

(untitled)
The article presents technological alliances as political activities, helping establish coalitions, co-opt supporters and eliminate rivals. Using the example of Microsoft’s and Google’s partner ecosystems, it discusses specific partnership techniques and their relevance for technology companies. The article offers a rich picture of developments of Microsoft Windows and Google Android platforms, combined with the steps taken by both companies to ensure support from partner firms. The effectiveness of financial, marketing and technological incentives as well as of deterrents depends on expected outcomes (such as: decreasing transaction costs, creating lock-ins, stimulating innovativeness or restricting development of competitive products) and technology life cycle stages. The article helps shape partnership strategies and optimize investments, needed to motivate and control partners.